2018
DOI: 10.1158/1538-7445.am2018-ct107
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT107: Ribociclib in combination with everolimus and exemestane in men and postmenopausal women with HR+/HER2− advanced breast cancer after progression on a CDK4/6 inhibitor: Efficacy and safety results from phase II of the TRINITI-1 study

Abstract: Background: Combining endocrine therapy (ET) with a cyclin-dependent kinases 4 and 6 (CDK4/6) inhibitor significantly improves progression-free survival (PFS) over ET alone in patients with hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2−) advanced breast cancer (ABC). However, optimal management of disease that progresses on this therapy is not established. In Phase 1 of the TRINITI-1 study (ClinicalTrials.gov identifier: NCT02732119), continuous ribociclib 300 mg/d + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Preliminary results from the initial 1008 patients with any menopausal status enrolled with 56 days of follow-up demonstrated a safety profile of ribociclib plus letrozole consistent with that of the MONALEESA-2 trial of postmenopausal women receiving first-line treatment for HR+, HER2-ABC [35]. Another ongoing trial, the TRINITI-1 trial (ClinicalTrials.gov identifier: NCT02732119), is investigating the effects of continuing a CDK4/6 inhibitor through triplet therapy (ribociclib plus everolimus plus exemestane) in patients with disease progression on a CDK4/6 inhibitor [36]. Furthermore, the disposition of ribociclib in the CNS is also being investigated in preclinical and early clinical studies.…”
Section: Discussionmentioning
confidence: 90%
“…Preliminary results from the initial 1008 patients with any menopausal status enrolled with 56 days of follow-up demonstrated a safety profile of ribociclib plus letrozole consistent with that of the MONALEESA-2 trial of postmenopausal women receiving first-line treatment for HR+, HER2-ABC [35]. Another ongoing trial, the TRINITI-1 trial (ClinicalTrials.gov identifier: NCT02732119), is investigating the effects of continuing a CDK4/6 inhibitor through triplet therapy (ribociclib plus everolimus plus exemestane) in patients with disease progression on a CDK4/6 inhibitor [36]. Furthermore, the disposition of ribociclib in the CNS is also being investigated in preclinical and early clinical studies.…”
Section: Discussionmentioning
confidence: 90%
“… 38 , 54-60 Emerging studies support a strategy for suppression of CDK4/6 activity combined with inhibition of PI3K/AKT/mTOR signaling to overcome CDKi resistance; however, no single gene alteration in the PI3K pathway has proven predictive of survival, suggesting that redundancies in the PI3K signaling network influence oncogenic potency. 6 , 37 , 38 , 50 , 51 , 54 , 55 , 58-61 Mutational profiling available in a subset of our cohort revealed a preponderance of mutations in constituents of the FGFR/FGF and PI3K/AKT/mTOR pathways, which have known crosstalk mediating CDKi and endocrine resistance. 13 , 62 Particularly, we observed that patients harboring a PTEN mutation before initiation of CDKi had significantly shorter post-CDKi PFS and 6 times the odds of experiencing rapid disease progression.…”
Section: Discussionmentioning
confidence: 91%
“…TRINITI-1 was a phase II trial combining ribociclib with everolimus and exemestane in patients who experienced progression on CDK 4/6 inhibition with AI. 54 An appreciable clinical benefit rate of 39.5% was seen. Further randomized trials studying this strategy are ongoing.…”
Section: Targeting Mechanisms Of Endocrine Resistance: Mtor and Pi3kmentioning
confidence: 92%